Potential of Surface Enhanced Raman Scattering for Catalytic Research - Alexander Wokaun; Alfons Balker (CHIMIA)
Present investigations of catalytic reaction mechanisms increase the demand for direct spectroscopic observation of the molecular processes occuring at the catalyst surface. Interdisciplinary research is essential to advance our knowledge in this field. We have therefore decided to explore the application of surface enhanced Raman scattering (SERS) for the in situ characterization of solid state catalysts. The fascinating phenomenon of surface enhancement is outlined in this article. The high sensitivity achieved is used to study amination reactions of aliphatic alcohols on copper catalysts. Results from surface enhanced Raman spectroscopy provide information on the mechanism which complements the evidence obtained from chemical and kinetic investigations. Enhanced Raman spectra of adsorbates have been recorded on-the surface of a technical copper catalyst under reaction conditions. The design of this substrate has been guided by combining the conditions for strong surface enhancement with the requirements for a catalyst that is stable at elevated temperatures in the presence of surface active adsorbents. The scope of SERS as a novel surface analytical tool in catalysis is evaluated, and an outlook to envisaged applications is given.